Performance index in MHD duct nanofluid flow - past a bluff body at high Re - Arjun, Kozhikkatil Sunil (Strojniški vestnik, 2017)
The quasi-two-dimensional Alsub2Osub3 -water nanofluid magneto hydro-dynamics (MHD) flowing over a circular cylinder at higher Reynolds number has been modelled using Ansys FLUENT 15.0 in a rectangular duct to determine the viability of heat transfer enhancement. The effect of the numerical simulations on performance indices were analysed for the range of 1000 -3000 Reynolds numbers, 10-100 modified Hartmann numbers, 0.5-2 nanoparticle volume concentrations, 0.1_0.4 blockage ratios, 1-0.25 position ratios, 0.75-1.5 gap ratios and 0-10 distance downstream of cylinder along heated duct wall. The results are presented graphically and discussed quantitatively. Grid independence is achieved with the domain having 3 upstream and 20 downstream cylinder diameter distance lengths with element polynomial degree 7 with respect to mean drag coefficient and Strouhal number. Cylinder placement with gaps to the heated wall of diameters between 0.75 and 1.25 and 10 diameters downstream of cylinder performed best, achieving 117 % enhancement of the performance indices at Re = 3000, Ha = 20, fi= 2 %, beta= 0.4 %, gama= 1 and G/d = 1. The performance indices were greater than one for all the cases tested, which indicates that the heat transfer enhancement for this flow is viable. The Nusselt number values of the present study were compared with the analytical and experimental data published earlier and found to be in perfect agreement validating the reliability of the present model.
Keywords: izboljšan prenos toplote; krožni valj; magnetohidrodinamika; nanofluidi; nanotekočine; računalniška dinamika tekočin; zastojno telo